Konsep Ideal Pengajuan Justice Collaborator dalam Pemeriksaan Perkara Tindak Pidana Korupsi: Konsep Silang Perkara, Mekanisme Hubungan Kontraktual dan Assesment - Luqmanul Hakim; R Lina Sinaulan; Joko Sriwidodo (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
A justice collaborator (JC) in Indonesia is a term for a criminal who is willing to cooperate with law enforcement to uncover larger, more organized criminal cases. JC status is regulated by Indonesian law and provides protection and rewards for those who qualify. The implementation of the role of justice collaborator (JC) in specific crimes, such as corruption, terrorism, and narcotics, has a deep background and rationale. This concept was born from the awareness that these crimes are often complex and organized, making them difficult to uncover using conventional law enforcement methods. On the one hand, in Indonesia, although the concept of justice collaborator has been adopted, several shortcomings are known, such as the lack of an assessment system for submitting witnesses who wish to cooperate with law enforcement, an assessment of the evidence and statements to be presented by witnesses, and an assessment of the rewards that witnesses deserve for their assistance and cooperation. The research method used in this study is a normative juridical research method. The materials reviewed are primary, secondary, and tertiary legal materials. The results of the study show that the concept of justice collaborator still has several shortcomings, including the lack of regulation of which institution has the authority to submit and determine the status of Justice Collaborator, the absence of regulations on cross-examination of witnesses in cases involving justice collaborators, the absence of a clear assessment system for the Justice Collaborator submission process, the evidence presented by Justice Collaborators, and the assessment of awards that Justice Collaborators deserve for their contribution in revealing cases, as well as the absence of regulations on contractual relations between law enforcement and Justice Collaborators